2019
DOI: 10.1042/bsr20192721
|View full text |Cite
|
Sign up to set email alerts
|

Association between polymorphisms in interleukin-18 promoter and risk of coronary artery disease: a meta-analysis

Abstract: Background: Previous studies have explored associations between interleukin-18 (IL-18) promoter polymorphisms and coronary artery disease (CAD). However, the results were controversial. We conducted a meta-analysis to clarify the association between the two polymorphisms and CAD risk. Methods: We searched English and Chinese databases and calculated the odds ratio (OR) and 95% confidence interval (CI) to estimate whether there are genetic associations between IL-18 promoter polymorphisms and the risk of CAD. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…For -607C/A, the overall OR related with a decreased risk of CAD in different genetic models including allelic (OR=0.8), recessive (OR=0.7) dominant (OR=0.7), homozygous (OR=0.6), and heterozygous models (OR=0.7). Additionally, IL-18 polymorphisms were associated with MI and multivessel (MV) disease [ 143 ]. Overall, genetic variation of the IL-18 can regulate the production of IL-18 and could potentially predict future coronary events.…”
Section: Genetic Evidencementioning
confidence: 99%
“…For -607C/A, the overall OR related with a decreased risk of CAD in different genetic models including allelic (OR=0.8), recessive (OR=0.7) dominant (OR=0.7), homozygous (OR=0.6), and heterozygous models (OR=0.7). Additionally, IL-18 polymorphisms were associated with MI and multivessel (MV) disease [ 143 ]. Overall, genetic variation of the IL-18 can regulate the production of IL-18 and could potentially predict future coronary events.…”
Section: Genetic Evidencementioning
confidence: 99%
“…Also, a meta-analysis of 15 studies published by Lian et al, suggested that the -137 polymorphism and the -607 polymorphism in the IL-18 promoter were associated with CAD and its consequences. [ 29 ] The information presented by Tiret et al [ 28 ] in 2005 is confirmed by the analysis of the data.…”
Section: Discussionmentioning
confidence: 59%
“…In addition to RA predisposition, increasing evidence on the association between IL-18 polymorphisms and other disease conditions has also been reported by systematic reviews and meta-analyses. The -607 C/A and/or -137 G/C polymorphisms in IL-18 may confer susceptibility to tuberculosis, especially in Asians [33]; inflammatory bowel disease, including both Crohn's disease and ulcerative colitis in Asians and Africans [34][35][36]; vasculitis [37] and systemic lupus erythematosus in Europeans and Asians [38]; Behcet's disease [39], various types of liver diseases [40,41], hepatitis B virus in East Asians and hepatitis C virus infection in South Asians [42] and Asian populations [43]; diabetic nephropathy in Asians [44]; allergic asthma and allergic dermatitis [45][46][47], Alzheimer's disease in Asians [48,49]; periodontitis [50], coronary artery disease in East Asians [51,52]; head and neck cancer risk, especially nasopharyngeal cancer, in Asian populations [53]; breast cancer in East Asians from China [54,55]; and prostate cancer in Asian and Caucasian populations [56]. IL-18 has been reported to be a potential clinical biomarker.…”
Section: Discussionmentioning
confidence: 99%